The Relationship Between Learning From Failures and Crisis Preparedness: the Determinants of Organizational Change - Imamoglu, Salih Zeki; Kocoglu, Ipek; Ince, Huseyin; Keskin, Halit; Polat, Murat; Akgun, Ali Ekber (Ankara Haci Bayram Veli Univ, 2013)
The increased complexity and uncertainty in the organizational environment makes organizational change an indispensable part of organizations' survival. This study suggests that organizational change is a concept that has to be examined within the dynamic conditions of the environment, under which organization operates, and proposes that learning from failures and crisis preparedness are the determinants of organizational change. In this context, the effects of learning from failures and crisis preparedness on organizational change as well as the relationship between these two variables have been empirically investigated. In order to test the research hypotheses, data collected from 155 firms have been through structural equation modeling using AMOS 4.0 software. The results of the analysis have supported the hypotheses. Lastly, the findings and managerial implications are discussed.
Keywords: Learning from failures; crisis preparedness; organizational change; crisis